AN ANALYSIS OF SAFETY LEVEL OF METAL CONTAMINANTS IN RIVER HADEJIA CATCHMENT, KANO REGION, NIGERIA - Bichi, A. A.; Butu, A. W.; Gadanya, M. A. (FUDMA JOURNAL OF SCIENCES, 2023)
The aim of this study is to analyze safety level of some metal contaminants in water in River Hadejia. Water samples were collected using manual method (simple grab method). Multiple samples were taken systematically and span for ten months to cover dry and rainy seasons using stratified systematic sampling technique. The parameters considered for laboratory investigation were trace and toxic metals. Atomic Absorption Spectroscopy (AAS) technique was used foranalysis of the water samples. Descriptive statistics (Mean) was used on the data to examine the concentrations, comparisons of the data obtained from the study and the standards. The WHO (2011) and NSDWQ (2007) guidelines for drinking water quality were used as standards to compare with the laboratory analyzed values. The findings show that the level of concentration of some metals Mg (3.80mg/l against 0.2mg/l); Cr (0.53mg/l against 0.05mg/l); and Pb (2.53mg/l against 0.01mg/l) were above the WHO (2011) and NSDWQ (2007) standards which indicates that River Hadejia shows evidence of metallic contaminants. The sources of many chemical elements were linked to the geologic formations, weathering processes and anthropogenic activities. It is recommended that there should be continuous periodic water quality assessment of the river because of the dynamic nature of human activities taking place in the watershed, for efficient planning and management of our surface water resources.